PRODUCTION OF ARTILLERY IN LVIV IN THE XV–XVIII CENT. AND PARTICIPATION OF THE UKRAINIANS IN IT - П. П. Ткачук; А. І. Харук; М. А. Верхотурова (Storìnki Istorìï, 2020)
The article describes the events that accompanied the process of the appearance, production, and decline of artillery production in Lviv in the XIV–XVIII centuries. The factors that have become prerequisites for setting up the production of guns in Lviv are analyzed. An important factor influencing the development of metalworking and weapons production in Lviv was the rich deposits of marsh ore from the Dniester along the Zubra River valley to Lviv. Long before the casting of artillery in the city was already pouring bells. Due to its favorable geographical location, Lviv was an important center of trade and crafts, which in turn contributed to the rapid emergence of new weapons in the city. The initial period of development of artillery production is characterized, the preserved Lviv bell tower of the XІV century is described from the holdings of the Museum of the Polish Army, it was concluded that its design corresponds to the requirements of the time.